2000
DOI: 10.1034/j.1399-3070.2000.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of aerobic activity on refuse temperature rise, I. Landfill experimental study

Abstract: The temperature field in a landfill situated in the south of France has been characterized and analysed. Sixty‐four probes, measuring temperature and gas composition, were placed directly in municipal solid waste during the filling of a 200 000‐m3 cell and the spatial and temporal temperature variations recorded. The average temperature increase was about 20°C. It occurred within the first 20 days. The thermal properties of the waste (conductivity and diffusivity) were measured with a thermal shock probe. A he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…As a result, this experimental simulation confirms the observations and the heat balance in landfills (Lefebvre et al, 2000): • the increase of the waste temperature during landfilling occurs with the aerobic decomposition of freshly disposed refuse; • the thickness of the aerobic zone obviously depends on both the biological oxygen consumption and the oxygen diffusion rates; a vertical oxygen gradient appears rapidly within two days and consequently, the temperature increases rapidly, then remains stable after two weeks; and • most of the accumulated heat is then conserved in anaerobic conditions because of the low thermal conductivity of the waste.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…As a result, this experimental simulation confirms the observations and the heat balance in landfills (Lefebvre et al, 2000): • the increase of the waste temperature during landfilling occurs with the aerobic decomposition of freshly disposed refuse; • the thickness of the aerobic zone obviously depends on both the biological oxygen consumption and the oxygen diffusion rates; a vertical oxygen gradient appears rapidly within two days and consequently, the temperature increases rapidly, then remains stable after two weeks; and • most of the accumulated heat is then conserved in anaerobic conditions because of the low thermal conductivity of the waste.…”
Section: Resultssupporting
confidence: 87%
“…The absence of aerobic A rough thermal balance showed that 80% of the heat accumulated in the waste was provided by the consumption of the oxygen transferred inside the model waste during filling (for details on the calculations, see Lefebvre et al 2000). Initially, the pores of the new fresh model waste were full of oxygen (21%) and from 10 cm depth, the oxygen concentration decreased rapidly with increasing depth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations